Habibie & Ainun - Habibie, B. J. (Bacharuddin Jusuf), 1936- (Jakarta, Indonesia : THC Mandiri, 2010)
Autobiography of B.J. Habibie with his wife Ainun Habibie.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Habibie, B. J. -- 1936- -- Marriage; Habibie, B. J. -- 1936- -- Family; Habibie, Hasri Ainun, -- 1937-2010.; Presidents -- Indonesia -- Biography